Antimutagenicity and induction of antioxidant defense by flavonoid rich extract of Myrcia bella Cambess. in normal and tumor gastric cells. (24th December 2015) - Serpeloni, Juliana Mara; Leal Specian, Ana Flávia; Ribeiro, Diego Luis; Tuttis, Katiuska; Vilegas, Wagner; Martínez-López, Wilner; Dokkedal, Anne Lígia; Saldanha, Luiz Leonardo; de Syllos Cólus, Ilce Mara; Varanda, Eliana Aparecida
Abstract: Ethnopharmacological relevance: The Brazilian "Cerrado" is an important source of natural products, such as Myrcia bella Cambess (MB, also known as "mercurinho"). MB leaves are popularly used for the treatment of diabetes and gastrointestinal disorders; however, only its hypoglycemic activity has been experimentally described. Aim of the study: Because MB is used to treat gastrointestinal disorders, the present study characterized biological activities of hydroalcoholic MB extract in human normal and tumor gastric cells. Materials and methods: Cytotoxic, antiproliferative, genotoxic and protective effects were evaluated, as well as the effects of the MB extract on gene expression. Results: The MB extract induced cytotoxicity in tumor cells at lower concentrations compared with normal cells as assessed by the MTT assay. Moreover, the MB extract induced necrosis based on acridine orange/ethidium bromide staining. An antiproliferative effect was evidenced through an arrest in the G2/M phase detected by flow cytometry and a decrease in the nuclear division index using the c ytokinesis-block micronucleus cytome assay . Cells treated with MB extract combined with doxorubicin (DXR) showed increased NUBDs, which may be related to the gene amplification of CCND1. Antimutagenic effects were also observed and may be associated with the antioxidant activities detected using the CM-H2 DCFDA probe. Conclusions: Our findings showed the following: (a) high concentrations of MB induced cytotoxicity and cell death by necrosis; (b) its antiproliferative effect was associated with G2/M arrest; and (c) its antioxidant activity could be responsible for the observed antimutagenic effects and for protective effects against gastrointestinal disorders previously described to MB. Although these effects are not specific to normal or tumor cells, they provide a panel of biological activities for further exploration. Graphical abstract: Myrcia bella extract at high concentrations decreases cell viability as demonstrated by MTT assay.Apoptosis/necrosis assay showed that cell death occured through the induction of necrosis process.At these high concentrations, MB also presented an antiproliferative effect as demonstrated by cell proliferations curves and flow cytometry. At 100 μg/mL, a small antiproliferative effect was demonstrated by flow cytometry and nuclear division index (NDI). Frequency of micronucleated cells did not change, however, a moderate increase infrequency of NUBDs was observed. This concentration also presented antimutagenic effect that could be related to antioxidant activity detected by CM-H2 DCFDA probe.